Furcellaran/gelatin hydrolysate/rosemary extract composite films as active and intelligent packaging materials - Jancikova, Simona; Jamróz, Ewelina; Kulawik, Piotr; Tkaczewska, Joanna; Dordevic, Dani (International journal of biological macromolecules, 2019)
The study investigated the active and intelligent properties of films based on furcellaran (FUR), gelatin hydrolysate (GELH) and rosemary extract (from fresh leaves (FRE) and dry leaves (DRE)). Rosemary extracts were blended with FUR/GELH film forming solution at different three concentrations (5, 10, 20%). Analyzing the ζ-potential dependences of complexation polysaccharide-protein hydrolysate, we selected optimal ratio for the film formation. The introduction of rosemary extracts into FUR/GELH films increased thickness, water content and tensile strength. The UV barrier properties of tested films improved with the addition of rosemary extracts into FUR/GELH matrix. The antioxidant activity (DPPH and FRAP) did not improved with the addition of FRE but significantly increased with the addition of DRE, reaching 88% of DPPH inhibition and 207 of μmol Trolox/g of dried film of FRAP value. The color changes in different pH were observed, however, the fish spoilage test showed that those films are not suitable as intelligent films for monitoring freshness of this type of food product. Among all films tested, FUR/GELH film with 20% DRE exhibited the best performance. The obtained results suggested that FUR/GELH films with 20% DRE could be used as a promising active food packing material.
Keywords: fyzikální jevy; algináty; Plant Extracts; ryby; rozmarýn; Protein Hydrolysates; Plant Gums; obaly potravin; kůže; proteinové hydrolyzáty; želatina; Antioxidants; zvířata; Food Packaging; rostlinné extrakty; Alginates; Physical Phenomena; spektrální analýza; Biocompatible Materials; antioxidancia; Fishes; Gelatin; Spectrum Analysis; biokompatibilní materiály; Animals; Rosmarinus; Skin; rostlinné gumy